GREEN OPEN SPACE RESEARCH IN SUPPORTING SUSTAINABLE URBAN PLANNING EFFORTS: FOCUSED LITERATURE REVIEW - Kurniawan, Erfin (Nusantara Hasana Journal, 2025)
Green open spaces (GOS) are vital infrastructure for promoting ecological balance, improving urban livability, and enhancing climate resilience. Although their global importance is increasing, scientific advancements in GOS in landscape architecture remain fragmented and unevenly distributed. This study offers a thorough bibliometric analysis of GOS research to chart its global development, key themes and emerging areas. Data were sourced from the Scopus database (1968–2026) and examined using VOSviewer and Biblioshiny to identify the publication trends, collaboration networks, and thematic clusters. The findings indicate a significant increase in research output post-2015, influenced by global sustainability frameworks such as the Paris Agreement and Sustainable Development Goals. China, the United States, and the United Kingdom have emerged as leading contributors, whereas Indonesia and other Southeast Asian nations have shown increased involvement, especially in tropical urban settings. Keyword network analysis highlighted a conceptual shift from aesthetic and recreational views to transdisciplinary themes connecting nature-based solutions, ecosystem services, public health and urban resilience. These results emphasize the growing integration of landscape architecture with environmental science and policy-driven sustainability. Future research should focus on context-specific frameworks, digital and geospatial modeling, and equitable access to green spaces, particularly in regions vulnerable to climate change effects. This study reaffirms the role of landscape architecture in advancing GOS as adaptive, regenerative, and inclusive infrastructure for sustainable urban development.